PENGGUNAAN MODEL PEMBELAJARAN ADVANCED ORGANIZERUNTUK MENINGKATKAN HASIL BELAJARPADA MATERI MENERIMA QADA DAN QADAR SISWA KELAS VISD NEGERI 2 BOJONG - Piana, Yayan (Jurnal Sains Indonesia, 2022)
This Class Action Research has the title "Use of Advanced Organizer Learning Models to Improve Learning Outcomes in the Material of Receiving Qada and Qodar for Class VI Students of SD Negeri 2 Bojong". The aim is to find out the improvement of learning outcomes on the material of receiving Qada and Qodar students of class VI SD Negeri 2 Bojong through the use of the advanced organizer learning model. This research method is classroom action research. The research was carried out in 2 improvement cycles, and each cycle had 2 meetings. The subjects of this study were sixth grade students of SD Negeri 2 Bojong in 2013 on the subject of receiving Qada and Qodar. The number of students as many as 25 people, consisting of 12 boys and 13 girls. Data collection techniques in this study were carried out through activities in the form of: (a) action planning; (b) implementation of actions; (c) action observation; and (d) reflection. The results showed an average increase of 60 at the first meeting of Cycle I, to 68 at the second meeting of Cycle I, to 72 at the first meeting of Cycle II and to 83 at the second meeting of the second cycle. Meanwhile, from the completion process, there was an increase from 12% at the 1st meeting of Cycle I, to 28% at the 2nd meeting of Cycle 1, to 52% at the 1st meeting of Cycle II and to 88% at the 2nd meeting. From the above results, the value and percentage of completeness always increases in each cycle, both meeting 1 and meeting 2. So it can be concluded that the use of the advanced organizer learning model can improve learning outcomes in receiving Qada and Qodar material for sixth grade students of SD Negeri 2 Bojong.